Central, epenthetic, unmarked vowels and schwas: A brief outline of some essential differences - Veloso, João (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
In this study, we examine the nature and content of some phonetic/ phonological designations to refer to central vowels. Bearing in mind that epenthetic vowels and unmarked vowels are not always central vowels, we will argue in favour of a thorough distinction between these designations and propose the use of: 1. ‘Central vowels’ to label vowels articulated along the central axis the of oral cavity, 2. ‘epenthetic vowels’ to refer to postlexically inserted vowels in order to regularize exceptional consonant strings, 3. ‘unmarked vowels’ to indicate the most frequent epenthetic vowels of a language. Additionally, the term ‘schwa’ is judged not strictly necessary to phonetic and phonological description, since it does not clearly separate the different meanings associated with more transparent designations such as ‘central’ or ‘epenthetic vowels’.